ATF4 selectively regulates heat nociception and contributes to kinesin-mediated TRPM3 trafficking - Man-Xiu Xie (Nature Portfolio, 2021)
The molecular mechanisms mediating nociception are unclear. Here, the authors show that the Activating Transcription Factor 4 (ATF4) is important for the response to heat nociception in mice and ATF4 role in mediating protein trafficking in dorsal root ganglion neurons.